Analisis Kinerja Program Penanggulangan Kemiskinan Melalui KJKS BMT (Studi : Kabupaten Agam dan Kota Padang) - Sartika, Dewi (Jurnal Ekonomi, 2013)
This research is a descriptive research which used qualitative and quantitaative approach. The purpose of this research is to know about the performance of financial and non financial as the program to overcome the poverty through KJS BMT in Agam district and Padang city. The researcher using the primary and secondary data to gather the information for this research. The financial measurement is analyzed by varians between the actual performance (asset) and budget realization. The result showed that there were the increased of financial performance began with the year of 2010 to may 31 2012, where the good increased of financial occurred in the year of 2011, where the 82,32% the increased for Agam district and 27,36% for Padang city. The last evaluation indicator is the impact indicator which had been evaluated by 6 measurement indicators. The impact for Agam district was 40% (fair), and Padang had 47,78% evaluation percentage which is equal to fair.